Les femmes au tournant du siècle 1880-1940 : âges de la vie, maternité et quotidien - Institut québécois de recherche sur la culture., Denise; Lemieux (Institut québécois de recherche sur la culture,, 1989)
Pages: 1 vol. (398 p.) ;
Keywords: 1800-1899; 1880-1889; 1890-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; histoire et politique; inégalités; maternité; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques; travail

Justice, gender, and the family - Okin, Susan Moller (Basic Books, 1989)
This work is a feminist critique of modern political theory. The author sets out to show how the failure to apply theories of justice to the family not only undermines democratic values but has led to a major crisis over gender-related issues.
Keywords: amériques; approches et analyses; care; discipline; division sexuelle du travail; droit; droits des femmes*; famille; genre; mariage; maternité; militance; patriarcat; philosophie; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; états-unis

The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Verso, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis

Homeward bound: American families in the Cold War era - May, Elaine Tyler (Basic Books, 1988)
In the 1950s, the term "containment" referred to the foreign policy-driven containment of Communism and atomic proliferation. Yet in Homeward Bound May demonstrates that there was also a domestic version of containment where the "sphere of influence" was the home. Within its walls, potentially dangerous social forces might be tamed, securing the fulfilling life to which postwar women and men aspired. Homeward Bound tells the story of domestic containment - how it emerged, how it affected the lives of those who tried to conform to it, and how it unraveled in the wake of the Vietnam era's assault on Cold War culture, when unwed mothers, feminists, and "secular humanists" became the new "enemy." This revised and updated edition includes the latest information on race, the culture wars, and current cultural and political controversies of the post-Cold War era.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cold war; cours; discipline; division of household labor; division sexuelle du travail; famille; guerre froide; his4443; histoire; histoire des femmes*; histoire du féminisme; histoire et politique; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique; états-unis

Invisible Work - Daniels, Arlene Kaplan (Social Problems, 1987)
Our folk understanding of “work” focuses on those activities you “have to do” to get paid for them. Women's work is correspondingly devalued, for it is either unpaid or limited by the demands of the unpaid work in the home. This understanding also includes a moral force. One should contribute to society by working. This paper shows the restrictiveness of these commonsense understandings and discusses the kinds of work that consequently disappear from view. I focus especially on the work involved in the social construction of daily life and in the maintenance and development of institutions. Finally, I present the rationale for expanding the concept of work to include many activities not previously considered in the folk concept: a keener awareness of the work involved in social constructions serves to dignify the labor and engender respect for the workers who do it.
Keywords: discipline; histoire et politique; philosophie; projet charge mentale; sciences humaines; thématiques; travail; travail invisible

Le Bordel: Milieu De Travail Contrôlé - Lévesque, Andrée (Labour / Le Travail, 1987)
PENDANT LONGTEMPS, des milliers de femmes gagnèrent leur vie dans des bordels à Montréal. L'étude de leur milieu de travail pendant les années vingt et trente révèle une organisation hiérarchique et des conditions dont le contrôle échappait aux principales intéressées. L'appareil judiciaire et policier, les organisations de réformes sociales, le clergé et les médecins hygiénistes affectaient, par la tolérance ou la répression, le cadre dans lequel s'exerçait la prostitution. Plus directement, les souteneurs, les tenancières et leurs gérantes déterminaient les conditions quotidiennes de travail. Les changements observés pendant toute cette période sont plus imputables à la vigilance policière qu'aux fluctuations économiques ou aux efforts des travailleuses elles-mêmes.
Keywords: 1900-1999; 1920-1929; 1930-1939; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; his4550; histoire; justice sociale; montréal; premier cycle; prostitution; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; thématiques; travail; travail du sexe; travail du sexe-prostitution

Cheap amusements: Working women and leisure in turn-of-the-century New York - Peiss, Kathy Lee (Temple University Press, 1986)
Contenu: The Homosocial World of Working-Class Amusements – Leisure and Labor – Putting on Style – Dance Madness – The Coney Island Excursion – Cheap Theater and the Nickel Dumps – Reforming Working Women's Recreation.
Keywords: 1800-1899; 1900-1999; approches et analyses; cours; discipline; his4443; histoire; histoire des femmes*; histoire et politique; loisirs des femmes*; new york; premier cycle; périodes historiques; rapports sociaux de sexe; sciences humaines; sociologie; thématiques; travail; travail des femmes*

La gestion ordinaire de la vie en deux - Haicault, Monique (Sociologie du Travail, 1984)
A partir de données variées (entretiens, photos, films) sur la double journée de femmes en activité, l'article rend compte d'une analyse sur la gestion quotidienne du travail salarié et du travail domestique, spécifique de la place des femmes dans les rapports sociaux de classes et de sexe. L'empiétement d'un univers sur l'autre complique la gestion des espacestemps ; celle-ci ne peut être réduite à une addition de pratiques qui seraient isolables, stables et univoques. La charge mentale de la journée « redoublée » est lourde d'une tension constante, pour ajuster des temporalités et des espaces différents, mais non autonomes, qui interfèrent de manière multiplicative.
Keywords: approches et analyses; charge mentale; discipline; europe; france; inégalités; projet charge mentale; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; travail de reproduction; travail domestique

Production du sentiment amoureux et travail des femmes - Dayan-Herzbrun, Sonia (Cahiers Internationaux de Sociologie, 1982)
Il est important d'expliciter le rapport qui relie le vécu privé des femmes à leur vie professionnelle, et, sous la dépendance matérielle, de faire surgir la dépendance affective. Celle-ci est liée aux positions dissymétriques occupées par les hommes et les femmes dans la relation amoureuse, qui sont une des marques sociales de la différenciation sexuelle dans la société moderne
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; inégalités; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail